Analisis Perhitungan Biaya Oprasional Kendaraan (BOK) Bus Transjakrta Koridor VII di Jakarta - Abdul Gani Kamaludin; Dian Ardyahiya Ekawati; Marthaleina Marthaleina (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
PT Eka Sari Lorena Transport and PT Jakarta Mega Trans are the operators managing Transjakarta at corridor VII that serves route Kampung Melayu – Kampung Rambutan. The decision related to transport fares needs careful handling and wise policy because it has to bridge the gap of interest between the passengers and the transportation provider. Therefore, careful estimation and improvement are urgently required in calculating the operational cost of public vehicle as the basis of decision making. This study is conducted to find out the estimation of public vehicle operational cost of PT Eka Sari Lorena Transport, PT Jakarta Mega Trans and the operational cost based on SK Dirjen Nomor 687 year 2002. The calculation method referred to SK Dirjen No 687 year 2002. The result shows that the public vehicle operational cost of PT Eka Sari Lorena is RP 9.373,00/bus-km while PT Jakarta Mega Trans is Rp 13.010,00/bus-km. The estimation of public vehicle operational cost on that particular route is Rp 8.802,64/bus-km. The analysis of those two transportation providers reveals that there is a significant different component influencing the operational cost, that is the component of financing the human resources.